The Role and impact of financial sector aid on financial development and poverty reduction - KIM, Ji Mi (KDI School, 2015)
The paper empirically considers the impact of financial aid on the financial development and poverty reduction, which is closely related to the quality of policy. I build a panel of 77 developing countries and study 1974 to 2011 using econometric methodology, including system-GMM. I find that financial sector aid can be a driver of poverty reduction with sound policy : Financial sector aid has a significantly positive impact on developing countries
Thesis(Master) --KDI School:Master of Development Policy,2015